POTRET MASYARAKAT URBAN DALAM NOVEL METROPOP CRITICAL ELEVEN KARYA IKA NATASSA - Wanda, Winia; Hayati, Yenni; Nst., M. Ismail (Universitas Negeri Padang, 2018)
This article portrays the culture of entertainment, consumerism, pragmatism, secularism or profane lifestyle, hedonism, taste uniformity and instant culture in Ika Natassa's Critical Eleven metropop novel. The research is qualitative research and using descriptive method.Â Based on the results of data analysis found the portrait of urban communities in the novel metropop Critical Eleven as follows. First, entertainment culture, such as music, traveling to places of interest, shopping, sports, partying and more browsing the internet and chatting with friends through social media. Secondly, the culture of consumerism, such as buying expensive goods for toys and collectibles, the use of well-known brands as their fashion,